Expressive language abilities of boys with idiopathic autism spectrum disorder and boys with fragile X syndrome + autism spectrum disorder: Cross-context comparisons. (March 2020) - Hilvert, Elizabeth; Sterling, Audra; Haebig, Eileen; Friedman, Laura
Background and aims: Understanding the unique expressive language profiles of children with phenotypically similar, but distinct neurodevelopmental disorders, such as idiopathic autism spectrum disorder and fragile X syndrome with a co-diagnosis of autism spectrum disorder (fragile X syndrome + autism spectrum disorder), has both clinical and theoretical implications. However, comparative studies of these two clinical groups have been limited, and results have been inconsistent, partially as a result of different assessment methods being utilized. Thus, the current study compared the expressive language profiles of boys with idiopathic autism spectrum disorder and boys with fragile X syndrome + autism spectrum disorder and examined whether a similar linguistic profile emerged across different language sampling contexts: a semi-structured conversation and the Autism Diagnostic Observation Schedule. Methods: Eighteen boys with autism spectrum disorder ( Mage  = 13.25 years) and 19 boys with fragile X syndrome + autism spectrum disorder ( Mage  = 12.19 years), matched on autism spectrum disorder symptom severity and similar in terms of chronological age and mean length of utterance, participated in this study. Boys produced two language samples: one semi-structured conversation and one taken from the Autism Diagnostic Observation Schedule. Language samples were coded for talkativeness, lexical diversity, mean length of utterance, intelligibility, and repetitive or perseverative language. Results: Analyses revealed that boys with autism spectrum disorder produced language samples that were more lexically diverse and intelligible, and that included less topic perseveration compared to boys with fragile X syndrome + autism spectrum disorder. With regards to sampling context, boys in both groups were more talkative and produced longer and more intelligible utterances in their conversation sample compared to their Autism Diagnostic Observation Schedule sample. However, boys with autism spectrum disorder and fragile X syndrome + autism spectrum disorder used a higher proportion of topic perseveration during the conversation sample. Conclusions: Overall, we found similarities as well as distinctions in the expressive language profiles of boys with fragile X syndrome + autism spectrum disorder and boys with idiopathic autism spectrum disorder. Moreover, the Autism Diagnostic Observation Schedule sample elicited a relatively different language profile than the conversation sample for boys in both groups. Implications: These findings help to further elucidate the unique language phenotypes of boys with idiopathic autism spectrum disorder and boys with fragile X syndrome + autism spectrum disorder. Moreover, our findings indicate that multiple language samples may be needed to obtain a comprehensive account of a child's expressive language ability.